Upward pressure on wages and the interregional trade spillover effects under demand-side shocks - Patrizio Lecca; Martin Christensen; Andrea Conte; Giovanni Mandras; Simone Salotti (European Commission, Joint Research Centre (JRC), 2019)
The paper illustrates the effect of a permanent demand-side shock in the perturbed regions and the associated spillover effects in the non-perturbed regions using the RHOMOLO spatial-numerical general equilibrium model of the EU economy. We test to what extent gradual upward pressure on wages generated by a domestic increase in demand alters the magnitude of the economic impacts in the long-run and the degree to which this could result in changes in trade patterns. We also assess the size and the direction of the effects with varying trade substitution elasticities and under both perfectly and imperfectly competitive product markets.
Keywords: J31; R12; R23; R58; 330; rhomolo; region; growth; regional development policies; Regional policy spillovers; spatial general equilibrium